Vulnerability of soil organic carbon in artificially constructed urban green spaces: Linking soil organic carbon physical fractions, microbial dynamics, and soil properties - Ye Lim Park; You Jin Kim; Jun Ge Hyun; Claire Chenu; Gayoung Yoo (Geoderma)
Soils in urban green spaces are often artificially constructed and highly disturbed, yet their capacity for long-term carbon (C) sequestration remains underexplored. This study evaluates soil organic C (SOC) content and vulnerability in three types of urban green spaces, tree-only roadside greenery, belt-type roadside greenery, and urban parks, with a natural grasslands serving as a reference. We analyzed SOC physical fractions and microbial activity under varying soil structural and chemical conditions, using the SOC vulnerability index (SOCVI), defined as the ratio of labile to stable fractions, to assess SOC stability. Results show that urban parks and tree-only roadside greenery have 87% lower SOC content than grasslands on average, and they contain a disproportionately high fraction of labile C, which increases SOC vulnerability. Tree-only roadside greenery exhibited particularly high SOCVI primarily because, despite low overall C inputs, its microbial activity relative to SOC is high, leading to inefficient stabilization of SOC as stable fractions. This condition is further exacerbated by alkaline pH and compaction, which hinder effective C sequestration. Although belt-type roadside greenery achieved higher SOC content through additional C inputs from understory vegetation and slightly improved soil structure, its SOCVI remained high, indicating that increased C inputs alone does not ensure stabilization. Structural equation modeling identified that mean annual temperature (MAT), soil pH and glomalin-related soil protein (GRSP) as key regulators of SOCVI. These findings underscore that enhancing SOC sequestration in urban green spaces requires integrated management strategies that optimize soil pH, improve structural properties, and support beneficial microbial activity alongside increased C inputs.